Efficacy of Mulberry Leaf (Morus alba L.) Mask in Reducing Acne Vulgaris among Vocational School Students - Sifatun, Avivatuz Zahroh; Rustanti, Elly; Fiddaroini, Fakhrun Nisa' (Fundamental and Management Nursing Journal, 2025)
Introduction: Teenage girls often experience acne due to hormonal changes. This condition not only affects their appearance but also lowers self-confidence and impacts their mental health. This study aims to determine the effect of the natural mulberry leaf mask formula (Mours alba L). on acne vulgaris in female students of Vocational School in  Jombang, Indonesia Method: The research design used was a One-Group Pre-Experimental, Pre-Test-Post-Test. This study involved 65 students, with a sample of 20 respondents selected through Quota Sampling. Data were collected using observation sheets and analyzed with SPSS 25 using the Wilcoxon Test. Results: Before therapy, 15 respondents (75%) experienced moderate acne vulgaris. After therapy, 15 respondents (75%) experienced mild acne vulgaris. Statistical analysis showed a significance value of 0.000 < α (0.05). Conclusion: Regular use of a natural mulberry leaf mask is beneficial for acne healing. Mulberry leaves contain vitamins A, C, and E, alkaloids, and flavonoids, which act as antibacterials, reduce inflammation, and reduce oxidative stress. This formula can be used as an alternative treatment for acne vulgaris.